Enhanced disturbance mitigation in nonlinear time delay systems with applications to double boost converters in microgrid environments - Mohanapriya Saminathan; Deepa Kaliyaperumal; Gopalakrishnan Ennappadam Ananthanarayanan; Deepa Gupta; Varikuti Sai Soumya Reddy (Scientific Reports)
Abstract This study proposes an enhanced Smith Predictor (ESP) based Modified repetitive control (MRC) technique to develop a precise tracking performance of the input delayed double boost converter model, which is highly influenced by disturbances and saturation nonlinearity. A group of inequalities is derived on the basis of Lyapunov stability concept, which are in the form of linear-matrix-inequalities (LMIs) to guarantee the asymptotic stability and tracking performance of the considered delayed double boost converter. To be more specific, the proposed Lyapunov method not only provides the asymptotic stability of the system but also design the controller parameters when the feasibility of the derived LMIs are analyzed. The validation of the suggested ESP based MRC technique is confirmed through the simulation analysis and the corresponding outcomes from the considered double boost converter model. Moreover, the recommended control procedure yields better accuracy in tracking performance and disturbance elimination when comparing with the existing active disturbance methods such as improved equivalent-input-disturbance (IEID), parallel EID (PEID), higher-order EID (HEID) and EID based Smith predictor (SP) techniques.